Sustainable Exploration of Peat Water for Drinking Water Resilience in the Remote Community of Muara Enggelam - Ansahar Ansahar; Irkhamiawan Ma’ruf; Bondansari Bondansari; Sherly Trifena Karundeng (Malikussaleh University, Aceh, Indonesia, 2026)
Peat water is an abundant raw water source in tropical peatlands; however, its use for drinking water is constrained by its acidic pH, high colour, elevated levels of natural organic matter (NOM), and microbial contamination, all of which increase the risk of carcinogenic disinfection byproducts when chlorinated. In Muara Enggelam Village, Kutai Kartanegara Regency, communities rely heavily on peat water and incur high costs to obtain clean water from neighbouring areas. This study aimed to design a laboratory-validated hybrid water treatment system capable of producing potable water from peat sources in remote communities. Water samples were collected from upstream, downstream, and an existing community treatment unit and analysed for physical, chemical, and microbiological parameters. Raw peat water exhibited acidic pH (5.11–5.66), high colour (176–235 TCU), turbidity (21.8–85.9 NTU), elevated iron concentrations (0.2–0.4 mg/L), and severe microbial contamination. The existing community system effectively reduced turbidity and iron, but further reduced pH, leaving residual colour and detectable bacteria. Based on laboratory results and process evaluation, a four-stage hybrid system is proposed, consisting of pH neutralisation with quicklime, controlled coagulation–flocculation, multistage filtration using quartz sand, activated carbon, and ion-exchange resin, followed by ultraviolet disinfection to prevent disinfection byproduct formation. System sustainability is supported through a village-owned enterprise management model and community willingness to pay of IDR 50,000–150,000 per month. The proposed system demonstrates that peat water can be transformed into a safe, resilient drinking water source for remote tropical communities through an integrated technical and institutional approach.